Therapeutic Medication Errors in the Non-Healthcare Facility Setting Associated with Hospital Admission, 2000–2024 - Srija Nuguri; Sandhya Kistamgari; Hannah L. Hays; Natalie I. Rine; Nichole L. Michaels; Motao Zhu; Gary A. Smith (Journal of Medical Toxicology, 2026)
Abstract Introduction This study investigated the characteristics and trends of therapeutic medication errors reported to United States (US) poison centers that occurred in a non-healthcare facility setting and were associated with hospital admission. Methods Using a retrospective cohort design, National Poison Data System data from 2000 to 2024 were analyzed. US Census Bureau data were used to calculate population-based rates. Results There were 115,071 therapeutic medication errors that occurred in a non-healthcare facility setting and were associated with hospital admission reported to US poison centers from 2000 to 2024. Most involved females (55.5%), individuals > 49 years old (56.9%), a single substance (71.5%), or occurred in a residence (96.0%). In addition, 39.0% were admitted to a critical care unit and 53.3% were associated with a serious medical outcome, including moderate effects (45.4%), major effects (7.2%), or death (0.7%, n = 745). Cardiovascular drugs (24.7%), analgesics (18.2%), and antidepressants (11.3%) were most commonly involved. The overall hospitalized therapeutic medication error rate per one million US population increased by 196.9% from 7.06 in 2000 to 20.97 in 2024; the rate was highest among adults > 69 years old, females, and errors involving cardiovascular drugs. Of the 115,009 exposures in which at least one therapeutic medication error scenario was reported, the most common scenarios were “other incorrect dose” (23.6%), “wrong medication taken/given” (16.7%), and “inadvertently took/given medication twice” (13.9%). Conclusions These study findings highlight opportunities to strengthen prevention efforts targeting therapeutic medication errors, particularly among older adults and individuals using cardiovascular medications, which could meaningfully decrease associated morbidity, mortality, and healthcare costs.